Korean and Chinese citizens’ pandemic fatigue and related factors amidst the prolonged COVID-19 pandemic: Implications for risk communication - Yubin Lee; Chenyuan Qin; Minjung Lee; Jie Deng; Jue Liu; Myoungsoon You (PLoS ONE, 2025)
Pandemic fatigue has emerged as a significant public health challenge, particularly in countries that implemented prolonged COVID-19 public health and social measures (PHSM). Understanding the factors contributing to pandemic fatigue and its impact on adherence to health protective behaviors is essential for sustaining public engagement in long-term disease management. This study examines pandemic fatigue in China and South Korea, two countries that maintained prolonged COVID-19 public health and social measures, to identify key predictors and explore its relationship with health protective behaviors. Online surveys were conducted in March 2023 to measure pandemic fatigue levels. To examine the relationships between pandemic fatigue, its predictors (perceived risk, efficacy beliefs, and daily life changes), and health protective behaviors, linear regression and mediation effect analyses were performed. The results indicated that the level of pandemic fatigue was 3.67 in South Korea and 3.47 in China, which was higher than previous research. High efficacy beliefs were associated with lower pandemic fatigue in both countries, while daily life changes had mixed effects. Pandemic fatigue has a significant impact on the adoption of health protective behaviors, with the exception of the practice of resting when unwell. The findings highlight the necessity of reinforcing efficacy beliefs through risk communication for a sustainable pandemic response. Given that risk perception declined over time, traditional fear-based health messages may be less effective in prolonged pandemics. Instead, risk communication strategies that emphasize a sense of control and provide clear, actionable guidance may help sustain public engagement. Furthermore, addressing the daily life changes faced by citizens and creating environments that facilitate the adoption of health-protective behaviors (e.g., access to paid sick leave) are important as long-term pandemic strategies.